2016
DOI: 10.1002/sia.6032
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide nanotube film formed on carbon steel for photoelectrochemical water splitting: effect of annealing temperature

Abstract: Carbon steels (CSs) were anodized in an ethylene glycol solution containing 3 vol.% H 2 O and 0.1 M NH 4 F to coat with nanotube arrays film. The as anodized nanotube arrays film were annealed in argon atmosphere at various temperatures ranging from 250 to 550°C for 4 h. The morphology and crystal phases of the film developed after annealing processes were examined using field emission scanning electron microscopy, X-ray diffraction. Morphology transforms from nanobube arrays to nanotube bundles at 250°C, to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Many scientific efforts are focused on designing electrode materials that fulfill the most criteria for efficient water splitting. One of them is the use of self-supported nanostructured photoanodes formed directly by anodic oxidation (anodization) of particular metals, such as titanium [ 4 , 5 ], zinc [ 6 , 7 ], tungsten [ 8 , 9 ], iron [ 10 , 11 ], or tin [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many scientific efforts are focused on designing electrode materials that fulfill the most criteria for efficient water splitting. One of them is the use of self-supported nanostructured photoanodes formed directly by anodic oxidation (anodization) of particular metals, such as titanium [ 4 , 5 ], zinc [ 6 , 7 ], tungsten [ 8 , 9 ], iron [ 10 , 11 ], or tin [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, annealing can change the composition of anodized films. Studies have shown that through different annealing treatments, a metal iron oxide layer can be obtained with a mixture of different kinds of iron oxides such as hematite and magnetite. The important and stable oxidation states of tin are SnO 2 and SnO. The theoretical specific capacity of SnO 2 is almost 3 times that of carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…A aplicação de nanotubos também é variada, podendo ser aplicada em sensor de gases, aplicações biomédicas, baterias e em células fotoeletroquimicas73,74,28 . Também o método de anodização pode ser estendido para diversos materiais com Fe2O3 e Ta2O5, sendo uma técnica muito versátil na construção de nanoestruturas75,29 . O processo de anodização consiste de um ataque eletroquímico controlado sob uma tensão anódica.…”
unclassified